MULTIDRUG-RESISTANCE OF KLEBSIELLA PNEUMONIAE ISOLATED FROM A CLINICAL CAT IN PAYAKUMBUH, WEST SUMATERA - Juliadi Ramadhan; Ario Ridho Gelagar; Usma Aulia; Anna Zukiaturrahmah (Buletin Veteriner Udayana, 2025)
Antibiotic resistance has become an increasingly critical concern in veterinary medicine, particularly due to its significant implications for companion animal health. This study aimed to evaluate the antibiotic resistance patterns of Klebsiella pneumoniae isolated from clinical cases at a veterinary clinic in Payakumbuh City. Bacterial samples were obtained from hospitalized animal patients and identified through macroscopic observation and biochemical testing. Isolates confirmed as K. pneumoniae were subjected to antibiotic susceptibility testing using the Kirby-Bauer disk diffusion method. The antibiotics tested included gentamicin, ampicillin, and enrofloxacin—commonly used drugs in clinical veterinary practice. The results revealed that K. pneumoniae exhibited varying degrees of resistance, with the highest resistance observed to enrofloxacin (70%), followed by ampicillin (60%), and gentamicin (40%). These findings highlight the urgent need for prudent antibiotic use and provide a reference for more effective antimicrobial selection in managing K. pneumoniae infections in companion animals.